New factors in the control of antigen presentation by MHC class I and II proteins. (October 2022) - Neefjes, Jacques; Wijdeven, Ruud; Pang, Baoxu; Berlin, Ilana; Perrin, Priscillia; Cabukusta, Birol; Jongsma, Marlieke; Luimstra, Jolien; Ovaa, Huib
Abstract : The process of antigen presentation by MHC molecules is one of the best studied cell biological processes. Many aspects and factors have been defined at the cell biological, biochemical and atomic level. Yet, it is still difficult to explain the exact antigens presented by MHC molecules, and it is unclear whether all factors involved in antigen presentation have been defined. We and others have performed knock-out and silencing screens to identify additional factors involved in the control of MHC class I and MHC class II expression. These have resulted in new types of biology and I will present one such an example. However, the system may not be saturated with factors. I will present two other screens for factors in control of MHC class I and MHC class II expression. These screens indicate how DNA silencers control MHC class I expression and how factors controlling the endosomal system and other systems contribute to cell surface expression of MHC class I and MHC class II molecules. We are in the process of placing these factors in the known biology of antigen presentation.